(3eLGR GdbQBfs - (3YR GdOjf YHO GdYRjR Hf YHO GdSdGe Hf CHj GdbGSe GdTGaYj GdSdej GdOeTbj GdeUQj, SdWGf GdYdeGA YR GdOjf Hf YHO GdSdGe,J (B660 (3g` s ((3YHO GdeLjO Hf GdfHjg GdGQefi s)
(3ChdgG (B:s
(3jHJOF HaUd hddJYjjf HGdeUOQ Yf GdeaYhd CeKdI efgG bhdg gPG Ndb Gddg Gi eNdhb Gddg s
(3BNQgG (B:s
(3jfJgi HBNQ GdaUd GdSGHY hGdGQHYjf ai GdLeYI Hjf GdMbjbI hGdeLGR s
(3GdChQGb eVWQHI ai GdJLdjOs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B144s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1590s
Keywords: (3GdHdGZIs